Evaluation of the Effectiveness of a New Antimicrobial Active Packaging for Fresh Atlantic Salmon (Salmo Salar L.) Shelf Life - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Valenzuela-Bascunan, X; Galotto-Lopez, M (2012)
Nowadays, consumers demand for fresh, high-quality seafood products continues to climb, especially in affluent, developed nations. At the same time, there is increasing attention regarding improved utilization of seafood for human consumption; Atlantic salmon is the main species in Chile aquaculture, and most of the salmon are exported as fresh fish to USA. It is well documented that low storage temperature inhibit bacterial growth and biochemical degradation, thus facilitating prolonged shelf life. Partly freezing the outer fillet layer from -0.5°C to -2.0°C (superchilling) has proven to be more efficient in inhibiting biochemical changes and bacterial spoilage compared with traditional chilling. Nevertheless, antimicrobial active packaging offers the possibility to increase product shelf life through the reduction of the microbiological damage of the product during its transportation, and thus increasing consumer safety and health. The main objective of this study was to compare the effects of an active antimicrobial packaging on microbiological growth, sensory attributes and instrumental quality measurements of raw Atlantic salmon (Salmo salar) fillets. Flexible plastic films containing Thymol as antimicrobial agent were used for salmon packaging. Salmon were stored at 2°C, 4°C and 8°C. Analyses of aerobic mesophilic bacteria and psicrophilic bacteria count were carried out at 1, 3, 8, 11, 15 and 18 days. L*ab* colour evolution, overall sensorial properties and chemical evolution were studied. Application of active antimicrobial packaging for fillet salmon reduced the microbial count for least 18 days at 2°C. No modification of the sensorial properties was detected by the sensorial panel, indicating that the antimicrobial compound used in the present study, thymol, is compatible with salmon packaging. Copyright © 2011 John Wiley & Sons, Ltd.
Keywords: active packaging; thymol; salmon packaging